Analisis Kompetensi Pedagogik Guru Kelas IV di SD Islam Plus YLPI Riau - Wulandari, Suci; Siti Quratul Ain; Fitriyeni (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
Pedagogic competence has an important role in student learning motivation because with strong guidance and encouragement it is able to provide enthusiasm and encouragement so that students change. The success of a lesson depends on how the teacher manages the class and the students. Teachers are not only about how to educate children, but also can understand the characteristics, attitudes and needs of students in order to be able to design learning in the classroom well. This study aims to improve teacher pedagogical competence in class IV SD Islam Plus YLPI Riau. This research uses qualitative descriptive method. This study used three data collection techniques, namely interviews, observation, and documentation. The data analysis technique used is according to Meles and Huberman namely data reduction, data presentation, and drawing conclusions or verification results. The results of the study show that there is a teacher's pedagogic competence that really needs to be owned by a teacher because it affects the way a teacher teaches.